تطبيق طريقة العصف الذهني على أساس الذكاء المنطقي الرياضي وأثرها على الكفاءة النحوية لطلاب التخصص الأول بمؤسسة مركز العربية باري كديري/The Implementation of The Brainstorming Method Based on Mathematical-Logical Intelligence and Its Influence on Arabic Grammar Competence in of Takhassus Class Students at Arabic Center Pare Kediri - Syakur, Abd.; Zunairoh, Yuyun; Al Akiti, Ayman; Iqbal, Muhammad (UIN ANTASARI, 2023)
Most non-native students regard Nahwu as the most challenging subject. at Markaz Arabiyah, Nahwu teaching still applies a conventional method namely the lecture method and uses a few media. Therefore, the researcher offers an alternative method as a solution to solve the problems. In this case, this research aimed to know the influence of Brain Storming method based on Mathematical-Logical intelligence on student's competence in Nahwu subject. The method of this study is experimental with Quasi-Experimental Design which used Non-equivalent Control Group Design. The population consisting of 30 students of which 14 students are from the control class and 16 students are from the experimental one. The strategy of data collection used in this study consisted of test. The data analysis used a t-test. The result of this study showed that independent data of the T-Test Sample, it could be known that the Significance Value (2-Tailed) is 0,021 < 0,05 which meant that there were significant differences between the average of the experimental class and the control one. The influence and effectivity level of that method is taken from the N Gain Score test which showed 45,19% for the experimental class and 29,73% for the control class. It meant that the Brain Storming method is effective enough, while the conventional one is not effective